5x-(4+2x)=7(x+1)-4x

Simple and best practice solution for 5x-(4+2x)=7(x+1)-4x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-(4+2x)=7(x+1)-4x equation:



5x-(4+2x)=7(x+1)-4x
We move all terms to the left:
5x-(4+2x)-(7(x+1)-4x)=0
We add all the numbers together, and all the variables
5x-(2x+4)-(7(x+1)-4x)=0
We get rid of parentheses
5x-2x-(7(x+1)-4x)-4=0
We calculate terms in parentheses: -(7(x+1)-4x), so:
7(x+1)-4x
We add all the numbers together, and all the variables
-4x+7(x+1)
We multiply parentheses
-4x+7x+7
We add all the numbers together, and all the variables
3x+7
Back to the equation:
-(3x+7)
We add all the numbers together, and all the variables
3x-(3x+7)-4=0
We get rid of parentheses
3x-3x-7-4=0
We add all the numbers together, and all the variables
-11!=0
There is no solution for this equation

See similar equations:

| -7+2r=-5 | | -3c+8c=30 | | (-12+x)/5=2 | | 6n-8n=-2 | | 3/4c-8=21 | | x-4.25=-4 | | -4p+10=82 | | p-4=12-4p-3p | | 2x=7/8x-15 | | -{6m+8}=4{17-m} | | -4(u-12)=4 | | X-14=4x+28 | | -4z=-2-5z | | -15.6k=12.48-14.8k | | 4x=100 | | x=35x-7 | | .2x+.75=8 | | 13x-6+6x+8=70 | | (1/2)x=-7.3 | | -4b-5=1-3b | | 2x+12=3x+-31 | | 7x-4=2(x+8) | | 4x+2=3x-30 | | -4n-7=-4(1+n)-3 | | 16-7m=-3m-8 | | 6n+3+5=-28 | | (3x+15)°=105° | | 1/2(8x-4)=2(2x+5)-4x | | (3x+2)=(6x-5) | | 16-7m=-3m-8m | | -5(-3b-21)=30(6b-2) | | 5(2x+9=7(x+3) |

Equations solver categories